Prevalência e fatores associados aos enteroparasitos em pacientes HIV positivos atendidos no Serviço de Assistência Especializada de Pelotas - RS, Brasil - Krause, Luís Eduardo Barcellos (2009)
Enteric parasitic infections are worldly known and reach mainly the poorest countries. This problem becomes more serious when it is associated with the Human Immunodeficiency Virus (HIV) infection. The objective of the study was to understand the prevalence and the risk factors associated with the enteric parasites among AIDS patients and HIV-positive healthy carriers. Cross-sectional study was carried out at the single assistance health service specialized in HIV/AIDS on Pelotas, a city in southern Brazil. Out of 273 patients who were interviewed in this study, 19,8% had pathogenic enteric parasites, and the most frequent pathogens were Trichuris trichiura, Giardia lamblia and Ascaris lumbricoides. The prevalence of pathogenic enteric parasites was significantly higher (31,4%) among who were not undergoing antiretroviral therapy (HAART) than among who were undergoing HAART (13,0%). The frequency of opportunistic enteric parasites (Cryptosporidium spp., Cystoisospora belli and Strongyloides stercoralis) was low; and it was 1,9% and 2,4%, respectively, among who were and were not undergoing HAART. This difference was not statistically significant. People with lower socioeconomic status, who had domestic animals and were not undergoing antiretroviral therapy (HAART), would have more chance to suffer from enteric parasitic infection when contrasted with the compared groups. The study has shown that it is necessary to adopt and carry out preventive and diagnosis actions among HIV-positive patients.